Local CRH signaling promotes synaptogenesis and circuit integration of adult-born neurons - Garcia, Isabella (2014)
Neural activity either enhances or impairs de novo synaptogenesis and circuit integration of neurons, but how this activity is mechanistically relayed in the adult brain is largely unknown. Neuropeptide-expressing interneurons are widespread throughout the brain and are key candidates for conveying neural activity downstream via neuromodulatory pathways that are distinct from classical neurotransmission. With the goal of identifying signaling mechanisms that underlie neuronal circuit integration in the adult brain, we have virally traced local Corticotropin-releasing hormone (CRH)-expressing inhibitory interneurons with extensive presynaptic inputs onto new neurons that are continuously integrated into the adult rodent olfactory bulb. Local CRH signaling onto adult-born neurons promotes and/or stabilizes chemical synapses in the olfactory bulb, revealing a neuromodulatory mechanism for continued circuit plasticity, synapse formation, and integration of new neurons in the adult brain.